Performane of Activated Carbon Adsorption in Removing of Organic Pollutants from River Water - Khalaf Erabee, Iqbal; M. Ethaib, Saleem (International Journal of Engineering and Technology, 2018)
This study presents a water treatment process by using a down-flow fixed bed activated carbon contractor model. Two types of activated carbon (AC) used, powder and granular activated carbon from date pits as a raw material, the parameters tested are biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), total dissolved solid (TDS) and pH. The column diameter and bed depths are made constant, whereas the size of activated carbon is varies. The obtained removal efficiencies for sample of river water are 39.8% of BOD, 41.8% of COD, 81.8% of TSS and 67.7% of TDS for granular AC. For powdered AC the removal efficiencies of parameters are 34.7% of BOD, 17.6% of COD, 72.7% of TSS and 50% of TDS. The granular AC made from date pits is the best activated carbon because of low cost of raw material and it is widely applied for usage in the water or wastewater treatment, as it is very effective in terms of cost and performance to cater the increasing demand of clean water.